Typhoid fever in Jakarta, Indonesia 2017-2023: spatial clustering and seasonality of hospitalization data to inform better intervention - Mujiyanto Mujiyanto; Basuki Rachmat; Aris Yulianto; Made Agus Nurjana; Wawan Ridwan; Endang Puji Astuti; Doni Lasut; Pandji Wibawa Dhewantara (Geospatial Health)
Typhoid fever is one of the common enteric fevers in developing countries, especially in emerging metropolitan areas in Indonesia. Yet, studies on spatial and temporal distribution of tyhoid fever are lacking. This study was conducted to analyze retrospective hospital-based data at the village level over the period 2017-2023 to understand the spatial and temporal variation of typhoid fever in Jakarta. Spatial analyses were performed by Moran’s I and Local Indicators of Spatial Association (LISA) to examine spatial clustering of typhoid incidence and to identify high-risk villages for typhoid fever, respectively. Seasonal decomposition analysis was performed to investigate the seasonality of this infection. A total of 57,468 typhoid cases, resulting in a cumulative incidence of 533.99 per 100,000 people, were reported during the study period. The incidence was significantly clustered (I=0.548; p=0.001) at the village level across Jakarta. Statistically significant high-risk clusters were detected in the South and East of Jakarta that were heterogeneous over time. We identified seven persistent high-risk clusters in the eastern part of the city and two in the southern part. Moreover, the typhoid incidence showed a strong seasonality trend, significantly associated with monthly total rainfall (p=0.018). The study revealed a significant spatial variation with strong seasonality in typhoid incidence across the city suggesting a variation in transmission intensity and needs for effective public health interventions, especially in the high-risk areas. Improvement in water and sanitation facilities, hygiene awareness and surveillance are essential to help reduce typhoid transmission in Jakarta.